Meneguhkan Visi Moderasi dalam Bingkai Etika Islam: Relevansi dan Implikasi Edukatifnya - Fata Asyrofi Yahya (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The academic anxiety in this paper is the emergence of pesantren which is indicated to teach radical understanding in recent times so as to create a negative stigma toward the character of Islamic boarding school in Indonesia which has been the character of the rahmat lil ‘alamin. The focus of this paper is on ethical issues, where radicalism is not in accordance with the ethical teachings of Islam and against the current face of Islam in Indonesia. Therefore the first problem formulation is to reveal the values ​​of moderation contained in Islamic ethics with a philosophical approach and the second offers a model of ethical education in pesantren with an educational management approach. From the formulation of the first problem concluded that the values ​​of moderation in Islamic ethics reflected on the way of thinking and acting someone who always refers to maqaa sid al-shariah and consider aspects of ummahat al-fadail in the actualization space includes tadbir al-nafs, tadbir al-manzil and tadbir al-mudun. While the second problem formulation offers a model of Islamic ethics education comprehensively in boarding school by conducting reconstruction and curriculum development with approach of field of study and reconstructionist approach.